The Notion of Wind on Rossetti’s and Damono’s Literary Work - Ayundhari, Vidia (Lingual Journal of Language and Culture; Vol 11 No 1 (2021): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2021.v11.i01.p02, 2021)
Christina Rossetti and Sapardi Djoko Damono are two poets born in different nationalities. Both mostly drew simple poems using natural objects, such as wind. The wind as a symbol of poem writing seems more appealing towards the poets and also the readers to interpret. The paper discusses several poems involved wind as an element on Rossetti’s work. It also analyses “Angin 3” by Damono.